Analysis of the Photosynthetic Parameters, Grain Yield, and Quality of Different Winter Wheat Varieties over a Two-Year Period - Jurica Duvnjak; Zorana Katanic; Hrvoje Sarcevic; Valentina Spanic (Agronomy, 2024)
Due to increasingly frequent unfavorable climate changes, achieving a high grain yield of wheat is a challenge for breeders. The relationships between wheat productivity and photosynthesis traits are not very well understood during the growing season. This study investigated the effect of chlorophyll a fluorescence parameters (maximum quantum yield of primary photochemistry (TRO/ABS) and performance index on absorption basis (PIABS)) on grain yield and the yield-related and technological quality traits of six wheat varieties over two growing seasons. In the first growing season (2021/2022), grain yield was significantly positively correlated with 1000 kernel weight and TRO/ABS at the second measurement point (growth stage 25 (GS 25)). Only the highest-yielding variety Bubnjar (104.0 dt ha−1) showed values of TRO/ABS at the same significance level between the second and third measurement points. Due to elevated virus and disease infections in the second growing season (2022/2023), the grain yield of the investigated varieties decreased between 37.9% (Bubnjar) and 67.6% (Anđelka) relative to the first growing season. The three highest-yielding varieties (Bubnjar, Rujana, and Silvija) in 2022/2023 were the tallest, were later in maturity, escaped yellow rust pressure at the stem elongation stage more efficiently, and also showed the lowest increase in TRO/ABS at this stage (fourth measurement point at GS 47, compared to the third at GS 32). In addition, the highest-yielding variety Bubnjar showed the highest increase in PIABS at the last measurement (seventh) at GS 71 compared to the sixth (GS 69), thus maintaining the vitality of flag leaves at the grain-filling stage, while the other varieties showed a very small increase or even a significant decrease. Therefore, plant photosynthetic activity over the entire growing season contributes to crop productivity.